Penerapan Senam Ling Tien Kung Dalam Menurunkan Hipertensi Pada Lansia - Wahyuni, Iin; Utaminingtyas, Farida; Aditia, Dita Selvia; Safitri, Oktaria; Xanda, Adhesty Novita (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Application of Ling Tien Kung Movement Technique in Reducing Hypertension in the Elderly. Ling Tien Kung is an energy therapy movement technique that activates natural healing energy (Swee, 2015). The healing process in energy therapy is by restoring energy that has become weak, disturbed or unbalanced (Eden, 2018). Hypertension or high blood pressure is a disorder of the blood vessels that will result in the supply of oxygen and nutrients transported by the blood being blocked to the body's tissues that need it. With increasing age, the condition and function of the body decline, it is not surprising that the elderly have more complaints because the body's system no longer works as well as when they were young. The method used is direct application, application of Ling Tien Kung gymnastics. The materials used are counseling materials and doing Ling Tien Kung gymnastics. Participants in the elderly mother activity in Gunung Sari Village, Way Khilau District, Pesawaran Regency were 25 people. There was enthusiasm from the participants during the activity. Participants know the benefits and Ling Tien Kung gymnastics. Elderly mothers need to apply Ling Tien Kung gymnastics correctly in order to implement healthy living behaviors.